A New Angle on the Knobe Effect: Intentionality Correlates with Blame, not with Praise. (April 2016) - Hindriks, Frank; Douven, Igor; Singmann, Henrik
Abstract: In a celebrated experiment, Joshua Knobe showed that people are much more prone to attribute intentionality to an agent for a side effect of a given act when that side effect is harmful than when it is beneficial. This asymmetry has become known as 'the Knobe Effect'. According to Knobe's Moral Valence Explanation (as we call it), bad effects trigger the attributions of intentionality, whereas good effects do not. Many others believe that the Knobe Effect is best explained in terms of the high amount of blame attributed in the harm condition, and the low amount of praise attributed in the help condition. This Blame Hypothesis (as we call it) explains the high number of intentionality attributions in the harm condition in terms of the high degree of blame people ascribe, and the low number of intentionality attributions in the help conditions in terms of the low degree of praise people attribute. We replicated Knobe's original experiment and conducted a logistic regression on the results to probe more deeply into the relationship between attributions of intentionality and responsibility. The statistical analysis revealed a hitherto unknown interaction effect: intentionality correlates with blame, but not with praise. This interaction effect is consistent with the Moral Valence Hypothesis, but inconsistent with the Blame Hypothesis, as well as with two of the three other hypotheses discussed here.